Initial Selection of Explosive Materials for the Explosives Terrorism Risk Assessment - Rachel E. Gooding; George C. Emmett; David R. Bradley (International Society of Explosives Engineers, 2017)
The United States (U.S.) Department of Homeland Security (DHS) Directorate of Science and Technology (S&T) is using a probabilistic risk assessment (PRA) approach to evaluate the risks from terrorist use of explosive materials against the Homeland. A similar approach is currently being used to evaluate the risk from terrorist use of chemical, biological, radiological and nuclear materials.